Physical characteristics and the talent identification and development processes in male youth soccer: a narrative review - Kelly, A. L.; Williams, C. A. (Strength and Conditioning Journal, 2020)
Talent identification and development in male youth soccer are complex and multidimensional processes. The English Football Association "4 Corner Model" is often adopted by academies to support coaches and practitioners to implement a multidisciplinary approach to their talent identification and development framework. This holistic approach is characterized by technical/tactical, psychological, social, and physical attributes, which are central to academy recruitment and individual long-term athlete development. The aim of this narrative review is to provide a critical synthesis of the physical characteristics within this model, which facilitate talent identification and development, namely physical performance, growth and maturation, and the relative age effect.